DEVELOPMENT OF AN ANTIFUNGAL BIOPREPARATION BASED ON AZOLLA CAROLINIANA AND EVALUATION OF ITS EFFICACY - Raxmatova Zarina Bahronovna (TADQIQOTLAR, 2026)
Abstract. Azolla caroliniana is a rapidly renewable aquatic fern with a permanent symbiosis with the nitrogen-fixing cyanobacterium Anabaena azollae. Its biomass contains phenolics, flavonoids, pigments, lipids, tannins and other secondary metabolites that are relevant to antimicrobial and antioxidant performance. The aim of this study was to develop a literature-guided IMRAD manuscript that proposes a practical antifungal biopreparation based on A. caroliniana and defines a realistic efficacy-evaluation framework for laboratory validation. A comparative analysis of recent and foundational studies was used to identify the most promising extraction route, the most responsive target microorganisms, and the main quality indicators for product standardization. Published evidence indicates that methanolic extracts of A. caroliniana show the strongest documented activity against Geotrichum candidum, with a mean inhibition zone of 15 mm and a minimum inhibitory concentration (MIC) of 312.5 µg/mL, while activity against Enterococcus faecalis is moderate and Candida albicans remains largely insensitive in crude systems. Nutrient-starvation studies also show that phenolics, flavonoids and anthocyanins increase under controlled stress, suggesting that cultivation strategy can be used to improve raw-material bioactivity before extraction. Based on the synthesized evidence, the proposed biopreparation workflow includes biomass cultivation, low-temperature drying, solvent screening, activity-guided fraction selection, formulation into a stabilized liquid or wettable powder, and evaluation by agar diffusion, MIC determination, phytochemical profiling, stability testing and preliminary cytotoxicity. The article concludes that A. caroliniana is a promising but still under-optimized source of antifungal metabolites. The best near-term application is a species-specific biopreparation developed from medium-polar extracts and standardized against G. candidum. Further research should expand the fungal test panel, identify marker compounds, and establish safety and storage limits for real agricultural and food-protection use.